A framework of psychological compensation in attention deficit hyperactivity disorder - Merkt, Julia; Reinelt, Tilman; Petermann, Franz (Frontiers in Psychology, 2015)
The term compensation is widely used in the context of Attention Deficit Hyperactivity Disorder (ADHD), yet, it is neither defined nor theory driven. Adapting a model of psychological compensation (Bäckman and Dixon, 1992) to fit ADHD research is the aim of this review: We will (1) introduce the existing theoretical framework of psychological compensation, (2) discuss its applicability to ADHD and adapt the model to fit ADHD research, and (3) set up requirements for research on psychological compensation in ADHD. According to the framework psychological compensation can be inferred if a deficit (i.e., a mismatch between skill and environmental demand) is counterbalanced by the investment of more effort, the utilization of latent skills, or the acquisition of new skills. The framework has to be adapted because ADHD deficits are developmental and in individuals with ADHD compensation can appear independent of awareness of the deficit. A better understanding of psychological compensation in ADHD could foster diagnosis and interventions. Therefore, we suggest that future studies should follow a research design incorporating independent measures of deficit, compensation and outcome as well as include individuals who compensate for their ADHD related deficits.